DETERMINANTS OF POWER OUTPUT PERFORMANCE IN MICRO HYDROPOWER PLANTS: AN ANALYSIS OF OPERATING AND INTERRUPTION TIME - Aulia Rahmah; Dewi Triantini; Sahrum Nurhabib Yusuf (Jurusan Pendidikan Teknik Elektro, 2025)
This study quantitatively investigated the relationship between the output power (kW) of the Bungin Micro Hydropower Plant (MHP) and two independent variables, operating time (hours) and interruption time (hours), using multiple linear regression. The analysis aimed to identify dominant factors influencing energy production efficiency. The resulting regression model, expressed as: Power (kW) = 3656.1 − 1.52 (Operating Time) − 1.02 (Interruption Time), indicates a negative correlation between both operating and interruption times and power output. However, statistical significance testing (p = 0.01) revealed that only interruption time had a significant impact on Bungin MHP's output power. This finding aligns with theoretical expectations that increased interruption durations impede energy generation. While operating time also exhibited a negative coefficient, its effect was not statistically significant (p > 0.05) within this model. Thus, interruption time is identified as the primary determinant of Bungin MHP's energy production, underscoring the critical need for effective interruption management to optimize plant performance.